2016
DOI: 10.1016/j.acha.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Window-dependent bases for efficient representations of the Stockwell transform

Abstract: Abstract. Since its appearing in 1996, the Stockwell transform (S-transform) has been applied to medical imaging, geophysics and signal processing in general. In this paper, we prove that the system of functions (so-called DOST basis) is indeed an orthonormal basis of L 2 pr0, 1sq, which is time-frequency localized, in the sense of Donoho-Stark Theorem (1989). Our approach provides a unified setting in which to study the Stockwell transform (associated to different admissible windows) and its orthogonal decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 25 publications
(26 reference statements)
0
39
0
Order By: Relevance
“…We experimentally found (using the defined training set) that we should fix the mean weight thresholds (μ 4 , μ 5 ) and the weights applied to the total variations (γ 4 th frequency band when adjacent phase differences are larger than μ 4 -times its mean: γ 4 = 2.8 -Weight applied to differences of the 5 th frequency band when adjacent phase differences are larger than μ 5 -times its mean: γ 5 = 2.8…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We experimentally found (using the defined training set) that we should fix the mean weight thresholds (μ 4 , μ 5 ) and the weights applied to the total variations (γ 4 th frequency band when adjacent phase differences are larger than μ 4 -times its mean: γ 4 = 2.8 -Weight applied to differences of the 5 th frequency band when adjacent phase differences are larger than μ 5 -times its mean: γ 5 = 2.8…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, this is another advantage of the ST, along with the fact that it does not present cross-terms (unlike the Choi-Williams and Wigner-Ville transforms) [27]. Unfortunately, ST presents high computational cost and memory requirements, which represent an important drawback when computing large signals [4]. It is for this reason that Brown et al [6] presented a computationally efficient implementation of the ST called the general Fourier-family transform (GFT), which minimizes computational time and resources making possible its application for biomedical signal processing [5].…”
Section: Time-frequency Transformsmentioning
confidence: 99%
“…50 DOST preserves the phase information while avoiding redundant calculations of time-frequency information and therefore being computationally less expensive. 50,51 It has been shown that DOST potentially provides a better approximation of the image information compared to wavelet and fourier transforms, 52 with higher SNR over base line compression. DOST is known to be one of the best techniques for image texture characterization, and outperforms the discrete wavelet transform (DWT) method.…”
Section: G4 Discrete Orthonormal Stock-well Transform (Dost) Featmentioning
confidence: 99%
“…DOST is known to be one of the best techniques for image texture characterization, and outperforms the discrete wavelet transform (DWT) method. 52 A two-dimensional DOST algorithm was applied to CBCT and pCT datasets in order to estimate the matrix of DOST coefficients for each slice of the tumor. As shown in Table II the DOST coefficient matrix was divided into nine equal segments.…”
Section: G4 Discrete Orthonormal Stock-well Transform (Dost) Featmentioning
confidence: 99%
“…In [1], it is proven that the so called DOST-functions, P j,k,τ (t) = T τ 2 j 1 2 j/2 j∈Z j,k e 2πi ηt , j ∈ N, τ = 0, . .…”
Section: Introductionmentioning
confidence: 99%